KALIGRAFI ARAB TENTANG KEJADIAN MANUSIA MENURUT AL-QURAN DALAM KARYA SENI GRAFIS (STENCIL PRINT) - Eli Rosmita, Drs. Syafei, M.Ag. (Serupa The Journal of Art Education, 2019)
This Final Project aims to convey information to the public about how the process of human creation according to the Al-Quran through verbal language by visualizing verses about human events according to the Al-Quran through Arabic calligraphy (stencil print). which is expected to add knowledge the community and will know about this, not make a proud and arrogant person because remember how their process was created. The method in making this work, through several stages, namely: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization concepts and (5) Resolutions are then exhibited. Ten works were presented for the following: Marriage, Fertilization, Nutfa, Alaqah, Madghah, Izam and lahm, Nasyah, Nafikha-Ar Ruh, Birth.Kata kunci : Arabic caligraphy, human event , Stencil Print.